The Implementation of Prevention, Eradication, Abuse, and Illicit Trafficking of Narcotics (P4GN) Policy at the National Narcotics Board of Banyumas Regency in 2023 - Putra Awaludin Nufa; Indah Ayu Permana Pribadi; Ariesta Amanda; Chamid Sutikno; Zaula Rizqi Atika (Political Sciences Program Study, 2025)
This research is motivated by the increase in drug cases in Banyumas Regency in 2023 which ranks 3rd in Central Java. This study aims to determine how the Implementation of the Prevention, Eradication, Abuse, Illicit Trafficking of Narcotics (P4GN) Policy at the National Narcotics Agency of Banyumas Regency in 2023. This study uses a qualitative method with a case study approach and purposive sampling data collection techniques carried out through observation, interviews, and documentation. This research was conducted at the National Narcotics Agency of Banyumas Regency. The data analysis used is according to Miles and Huberman which consists of: data reduction, data presentation, and conclusions. The focus of this study is adjusted to the theory of George Edward III, namely: communication aspects, resource aspects, disposition aspects, and bureaucratic structure aspects. The results of the study show that the implementation of the P4GN policy at the BNN of Banyumas Regency has been running quite well in terms of communication, disposition, and bureaucratic structure. However, the resource aspect, especially human resources, is still the main obstacle in optimizing policy implementation. The conclusion of this study is that the implementation of the policy has not been fully effective due to limited resources owned by the implementing agency. It is necessary to increase the capacity of human resources as well as budget support and facilities to strengthen the implementation of the policy in the field. It is hoped that the results of this study can be input for the Banyumas Regency government and the Banyumas Regency National Narcotics Agency to evaluate and improve the implementation of the P4GN policy in the future, in order to significantly reduce the number of drug abuse in Banyumas Regency.